c - d; 9 (b, 2009)
Diary and autobiography of Abbasuddin Ahamad, folk singer from Bangladesh.
Includes Index.
In Bengali.
Keywords: Ahamad, Abbasuddin, -- 1901-1959.; Folk singers -- Bangladesh -- Biography; Lyricists -- Bangladesh -- Biography